Option Trading Strategies for Different Market Conditions for Hedging the Portfolio and Trading for Profits - Ramchandra, Mohite Trupti; Satish, Y. M.; Krishnamurthy, M. G. (Indian Journal of Finance, 2010)
Derivatives are among the most complex financial instruments and also one of the most controversial. While they are as old as commerce itself, they have become prominent only in the last few decades. Their supporters say that derivatives improve risk management and increase liquidity. Their critics claim that they make markets less transparent and more prone to instability and speculation. Both sides would agree that derivatives are extremely important and have a big impact on other financial markets and the economy. So even if the average investor doesn’t invest directly in derivatives, its important that he or she knows what they are.